Manajemen Bimbingan dan Konseling SMK Ma’arif NU 1 Bener - Madum, Mohamad (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2021)
This study aims to find out the advantages and disadvantages of the BK program at SMK Ma'arif NU 1 Bener so that it can be improved and developed even better. To find out the mechanism of the BK program at SMK Ma'arif NU 1 Bener, we use a comprehensive BK pattern to find out and understand what planning is being done in the comprehensive guidance and counseling service program. The comprehensive BK pattern itself is an effort to provide assistance to each student in order to develop their potential as optimally as possible. This research uses descriptive research method with survey type. Based on research conducted on the description of the implementation of the BK service management system at SMK Ma'arif NU 1 Bener, it is not yet in the high category that implements the BK service management system.